Recent advancements in wound management: Tailoring superwettable bio-interfaces - Zhong, Dongsheng; Zhang, Hongbo; Ma, Zhengxin; Xin, Qiangwei; Lu, Yongping; Shi, Ping; Qin, Meng; Li, Jianshu; Ding, Chunmei (Frontiers in Bioengineering and Biotechnology, 2022)
Skin tissue suffering from severe damages fail in self-regeneration. Proper wound dressings are highly demanded to protect the wound region and accelerate the healing process. Although large efforts have been devoted, there still exist disturbing dilemmas for traditional dressings. The exquisite design of bio-interface upon superwettable materials opens new avenues and addresses the problems perfectly. However, the advancements in this area have rarely been combed. In light of this, this minireview attempts to summarize recent strategies of superwettable bio-interfaces for wound care. Concentrating on the management of biofluids (blood and exudate), we described superwettable hemostatic bio-interfaces first, and then introduced the management of exudates. Finally, the perspective of this area was given. This minireview gives a comprehensive outline for readers and is believed to provide references for the design of superwettable materials in biomedical area.